Importance of multidisciplinary and regional collaboration in integrated West Nile virus surveillance - the "One Health" concept : Značaj multidisciplinarne i regionalne suradnje u integriranom nadzoru West Nile virusa - koncept "Jedno zdravlje" - Vilibić Čavlek, Tatjana (Array, 2020)
West Nile virus (WNV) is nowadays one of the most widely distributed arboviruses. In the last two decades, small or large WNV epidemics and epizootics are continuously reported in Europe. In this review, we present the epidemiological characteristics of WNV infections detected in Croatia and Serbia within the “One Health” context. Presented results confirm the importance of multidisciplinary and regional collaboration in the diagnosis and surveillance of this (re-)emerging viral zoonosis.